2017
DOI: 10.1089/aid.2016.0104
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Cardiovascular Health and Carotid Atherosclerosis in a Mixed Cohort of HIV-Infected and Uninfected Ugandans

Abstract: Preventable cardiovascular disease (CVD) risk factors are responsible for the majority of CVD-related deaths, and are increasingly recognized as a cause of morbidity and mortality for HIV-infected persons taking antiretroviral therapy (ART). Simplified tools such as the American Heart Association's ideal cardiovascular health (iCVH) construct may identify and prognosticate CVD risk in resource-limited settings. No studies have evaluated iCVH metrics in sub-Saharan Africa or among HIV-infected adults. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 54 publications
(51 reference statements)
6
30
2
Order By: Relevance
“…This is similar to, though larger in magnitude, a previous cross‐sectional finding in Uganda in which BMI mediated over 25% of the association between HIV and SBP . BMI appears to be a major contributor to the BP increase among people with HIV partly due to better access to care and healthier lifestyles (more exercise, cessation of smoking, and less salty/fatty diets) . Though HIV infection is associated with weight loss via multifactorial mechanisms including socioeconomic status, access to care, cultural practices, psychological factors, HIV virus, and ART, stabilization on ART leads to weight gain termed “trend toward normal weight.” Though beneficial to health recovery and return to pre‐HIV workforce productivity, this represents a trend toward overweight and obesity and later blood pressure increase …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is similar to, though larger in magnitude, a previous cross‐sectional finding in Uganda in which BMI mediated over 25% of the association between HIV and SBP . BMI appears to be a major contributor to the BP increase among people with HIV partly due to better access to care and healthier lifestyles (more exercise, cessation of smoking, and less salty/fatty diets) . Though HIV infection is associated with weight loss via multifactorial mechanisms including socioeconomic status, access to care, cultural practices, psychological factors, HIV virus, and ART, stabilization on ART leads to weight gain termed “trend toward normal weight.” Though beneficial to health recovery and return to pre‐HIV workforce productivity, this represents a trend toward overweight and obesity and later blood pressure increase …”
Section: Discussionsupporting
confidence: 80%
“…The Uganda Non‐Communicable Diseases and Aging Cohort (UGANDAC study ClinicalTrials.gov Identifier: NCT02445079) is a longitudinal cohort of ambulatory HIV‐infected adults stable on antiretroviral therapy (ART) for at least 3 years and matched population‐based, HIV‐uninfected controls in rural southwestern Uganda as described in detail previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the surrogate outcomes studied are diverse and reflect discrete vascular functions, the majority of studies showed increased atherosclerosis among PLWH, either versus controls or in relation to HIV disease duration or treatment status. Although some studies demonstrate no evidence for increased atherosclerosis among PLWH [ 78 , 92 ], most studies show early subclinical atherosclerosis by surrogate CVD outcomes [ 81 , 93 98 ]. A large Ugandan study demonstrated subclinical atherosclerosis via cIMT in 18% of PLWH attending clinic with higher risk among ART-experienced or older patients with elevated body mass index (BMI) or LDL [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study design is a longitudinal cohort study which aims to describe non-communicable disease morbidity and aging among an older, ambulatory population in rural Uganda. The cohort is comprised of two sub-groups: people over 45 years of age living with HIV (PLWH) on antiretroviral therapy (ART) in outpatient care and an age and sex-matched, HIV-uninfected, and population-based comparator group [25][26][27]. Participants are seen annually for completion of questionnaires, specimen collection, and cardiovascular diagnostic measurements.…”
Section: Study Populationmentioning
confidence: 99%